The Implementation of Antenatal Classes: A Scoping Review - Oktarina, Mika; Sulastri, Delmi; Utama, Bobby Indra; Firdawati, Firdawati (Asosiasi Pendidikan Kebidanan Indonesia (AIPKIND), 2025)
Background: Antenatal classes serve as a learning platform for pregnant women regarding pregnancy and childbirth preparation. This literature review aims to map the literature and evidence-based practices related to antenatal class implementation. Purpose: This scoping review aims to assess the implementation of Antenatal Classes. Methods: This study adopts a literature review design. Initial searches for journal articles were conducted on the PubMed, ScienceDirect, and Google Scholar databases from 2019 to 2024. The study identified 78 articles, of which only six journal articles met the inclusion criteria. Literature review procedures: collecting library data, reading, and note-taking, as well as critically assessing research materials. Results: According to the literature review, the implementation of antenatal classes yields numerous benefits, reducing stress and anxiety symptoms for both pregnant women and their partners in facing pregnancy and childbirth. Providing comprehensive and continuous material can enhance pregnant women's knowledge, attitudes, and behavior changes in preventing complications. Conclusion: Antenatal classes benefit mothers in preparing for a healthy pregnancy, childbirth, breastfeeding, transitioning into motherhood, and enabling early detection. Support from husbands and families to attend antenatal classes can boost the mother's confidence. A research gap identified for future studies is the variation in facilitators (healthcare professionals) of antenatal classes between developed and developing countries. Interprofessional Collaboration (IPC) is implemented in developed countries by involving specialized doctors, midwives, and nutritionists as facilitators in antenatal class implementation.